Diseases and Pests Associated with Avocado Plantation Intercropping with Mango and Durian in Watulembu, Wonogiri - Poerwanto, Mofit Eko; Wicaksono, Danar; Ulilalbab, Azizah Ridha; Ajri, Miftahul (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2024)
One of strategic fruit commodities was avocado that had high economic value. Pest and diseases were main problems faced by farmers. This study identified diseases and pest associated with avocado plantation intercropping with mango and durian in Watulembu district, Wonogiri Regency through symptoms and its controls. The observation was done to the abnormalities avocado plants and the field condition surrounding the planting area. It was conducted by visual observation, recorded using a digital camera, and then described and identified based on their symptoms and a literature review. The results of our observation were Algal leaf spot, Anthracnose, Sooty mold, and Planococcus citri. Pest and plant disease could be controlled by cultural technique, avoid plant stress, and also using chemical pesticide.